Road-safety data delivery in IP-based vehicular sensor networks. Issue 3 (4th May 2021) - Li, Yanli; Wang, Xiaonan
ABSTRACT: With the substantial increase in vehicle population, the road safety problems such as accidents have become serious. In this paper, we propose a road-safety data delivery solution in vehicular sensor networks to solve road safety problems and improve driving safety. The road-safety data delivery in vehicular sensor networks is delay-sensitive, so this solution aims to reduce the road-safety data delivery latency by shortening the addressing, routing and handover delays. In the proposal, a new address structure is proposed to achieve the road-safety data delivery. Based on the new address structure, the address configuration can be achieved without duplicate address detection and the routing can be performed without route discovery. Moreover, multiple sensor devices can achieve handovers via one handover operation without performing time-consuming care-of address configuration. Finally, the proposal is analyzed and evaluated, and the data shows that the proposal effectively reduces the road-safety data delivery latency. GRAPHICAL ABSTRACT: